On the relevance of the alpha frequency oscillation's small-world network architecture for cognitive flexibility. Issue 1 (December 2017) - Wolff, Nicole; Zink, Nicolas; Stock, Ann-Kathrin; Beste, Christian
Abstract Cognitive flexibility is a major requirement for successful behavior. nNeural oscillations in the alpha frequency band were repeatedly associated with cognitive flexibility in task-switching paradigms. Alpha frequencies are modulated by working memory load and are used to process information during task switching, however we do not know how this oscillatory network communication is modulated. In order to understand the mechanisms that drive cognitive flexibility, ERPs, oscillatory power and how the communication within these networks is organized are of importance. The EEG data show that during phases reflecting preparatory processes to pre-activate task sets, alpha oscillatory power but not the small world properties of the alpha network architecture was modulated. During the switching only the N2 ERP component showed clear modulations. After the response, alpha oscillatory power reinstates and therefore seems to be important to deactivate or maintain the previous task set. For these reactive control processes the network architecture in terms of small-world properties is modulated. Effects of memory load on small-world aspects were seen in repetition trials, where small-world properties were higher when memory processes were relevant. These results suggest that the alpha oscillatory network becomes more small-world-like when reactive control processes during task switching are less complex.